Perceived sustainability improves guest loyalty in hospitality sector - Dedat, Sajeeda; Rodrigues, Rosa Isabel (Frontiers in Sustainability, 2025)
IntroductionThis study explores how the environmental, economic, and social dimensions of sustainability influence guest loyalty and, subsequently, their intention to revisit the same hotel. It builds on the premise that positive perceptions of sustainable practices may play a critical role in strengthening the relationship between guests and hospitality brands.MethodsA cross-sectional survey was conducted with a sample of 348 hotel guests. The data were analysed using structural equation modelling and mediation analysis to examine the relationships among the key variables.ResultsFindings reveal that favourable perceptions of sustainability initiatives significantly enhance revisit intentions, with guest loyalty serving as a central mediating variable. The three pillars of sustainability exert distinct effects, underscoring the importance of adopting differentiated and targeted sustainability strategies in the hospitality sector.DiscussionThe study highlights the practical importance of clearly and authentically communicating sustainable actions to foster emotional engagement and long-term guest relationships. By demonstrating the strategic role of sustainability in building loyalty and encouraging responsible tourism behaviour, the findings challenge the assumption that all sustainability dimensions are equally effective. This research offers both theoretical refinement and actionable insights for hospitality managers seeking to integrate sustainability into the brand experience.